Recurrent Demyelinating Episodes as Sole Manifestation of Inherited CD59 Deficiency - Solmaz, Ismail; Aytekin, Elif Soyak; Çağdaş, Deniz; Tan, Cagman; Tezcan, Ilhan; Gocmen, Rahsan; Haliloglu, Goknur; Anlar, Banu (Neuropediatrics, 2020)
Defects in the regulatory components of the complement system can lead to inflammatory diseases. We present a patient who had four episodes of demyelination in the central nervous system as the only manifestation of inherited CD59 deficiency. Relapsing encephalopathy partially responsive to intravenous immunoglobulin and steroid treatments on the background of parental consanguinity suggested an inherited immune dysregulation. Next generation sequencing revealed homozygous mutation in the CD59 gene, confirmed by lack of CD59 expression on flow cytometry. Inherited CD59 deficiency is a rare autosomal recessive condition characterized by chronic hemolysis, recurrent strokes, and relapsing peripheral demyelinating neuropathy mimicking Guillain–Barré syndrome or chronic inflammatory demyelinating polyneuropathy. Recurrent central nervous system demyelinating episodes as the only manifestation has not been reported to date in inherited CD59 deficiency. This entity should be considered in the differential diagnosis of patients with early-onset recurrent neurological diseases with central or peripheral origin.
Keywords: immune dysregulation; CD59 deficiency; acute disseminated encephalomyelitis; multiphasic disseminated encephalomyelitis